DEVELOPMENT AND UTILITY OF GEOREFERENCED ANALYTICAL TOOLS IN RURAL AREAS - Andreas PAPANDREOU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this paper, is to investigate the planning and development a mapping, georeferenced and analytical tool and the utility of this, in agricultural sector. The methodological approach followed is based on the research of scientific approaches and scientific bibliography, also using technological innovations and aims at the overall assessment of the usefulness of such a technological development in agricultural sector. As a result of this research, it is considered that proper planning and optimal use of all the data held in their hands by farmers, is necessary so that they have sustainability in agricultural sector.